Delayed Replantation of Avulsed Teeth: Two Case Reports - Selcuk Savas; Ebru Kucukyilmaz; Merve Akcay; Serhat Koseoglu (Hindawi Limited, 2015)
This case report presents two cases of delayed replantation of avulsed maxillary central incisors after an extended dry extra-alveolar period. Eight-year-old boy and 10-year-old boy presented with avulsed maxillary central incisors due to trauma occurring 27 and 7 hours earlier, respectively. Treatment guidelines for avulsed mature/immature permanent teeth with prolonged extra-oral time were carried out for the teeth and the extra-oral endodontic treatment was completed. After having been repositioned, the teeth were stabilized for 4 weeks and prophylactic antibiotic was prescribed. Clinical and radiographic controls were done after 18 months for Case I and 12 months for Case II. During the follow-up periods the teeth reported in these cases have remained in a stable, functional position but revealed clinical initial replacement resorption and ankylosis.